2007
DOI: 10.1897/06-634r.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of the acute biotic ligand model for silver

Abstract: An important final step in development of an acute biotic ligand model for silver is to validate predictive capabilities of the biotic ligand model developed for fish and invertebrates. To accomplish this, eight natural waters, collected from across North America, were characterized with respect to ionic composition, pH, dissolved organic carbon, and sulfide. Tests were conducted with the cladoceran Ceriodaphnia dubia (48-h static) and the fish Pimephales promelas (96-h static renewal) to determine the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The acute toxicity of silver was also investigated by other researchers. Kolts et al (2006) reported a 48-h EC50 of 0.30 lg dissolved Ag/l while Bielmyer et al (2007) reported a 48-h EC50 of 0.76 lg dissolved Ag/l. Bielmyer et al (2007) also performed acute studies with C. dubia in HT water (non-reconstituted) and reported a 48-h EC50 of 1.28 lg dissolved Ag/l.…”
Section: Invertebrate Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The acute toxicity of silver was also investigated by other researchers. Kolts et al (2006) reported a 48-h EC50 of 0.30 lg dissolved Ag/l while Bielmyer et al (2007) reported a 48-h EC50 of 0.76 lg dissolved Ag/l. Bielmyer et al (2007) also performed acute studies with C. dubia in HT water (non-reconstituted) and reported a 48-h EC50 of 1.28 lg dissolved Ag/l.…”
Section: Invertebrate Studiesmentioning
confidence: 99%
“…Kolts et al (2006) reported a 48-h EC50 of 0.30 lg dissolved Ag/l while Bielmyer et al (2007) reported a 48-h EC50 of 0.76 lg dissolved Ag/l. Bielmyer et al (2007) also performed acute studies with C. dubia in HT water (non-reconstituted) and reported a 48-h EC50 of 1.28 lg dissolved Ag/l. For comparison, we observed a 48-h EC50 of 0.27 lg dissolved Ag/l in reconstituted HT water using a 5 min (approximate) equilibration period (Naddy et al 2007a).…”
Section: Invertebrate Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For a specific water body, the determination of water effect ratios (WERs) is crucial while generating site-specific AWQC (Di Bielmyer et al 2007). The WER is defined as the ratio of the effective concentration of the site-specific water to the effective concentration of the reference laboratory water.…”
Section: Site-specific Ambient Water Quality Criteriamentioning
confidence: 99%
“…The biotic ligand model (BLM), derived from the gill surface interaction model and the free ion activity model, has been widely used to predict the toxicological effects of metals on aquatic organisms in the last decade (Paquin et al 2000;Niyogi and Wood 2004;Bielmyer et al 2007). In the BLM, the metal toxicity is resulted from the free metal ions reacting with the binding sites (i.e., biotic ligand) at the site of action for aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%